Pengembangan Bahan Ajar Matematika Berbantuan Aplikasi Math City Map Pada Materi Bangun Datar Siswa Kelas VII SMP - Amanda Dinda Arum Nissa; Nurul A’in Fajaril (Media Informasi Penelitian Kabupaten Semarang, 2024)
Mathematics is a science that deals with studying abstract forms, so it requires teaching aids to make it clearer and more real. Developments in science and technology have occurred, one of which is Android-based learning media. The aim of this research is to develop mathematics teaching materials assisted by the Math City Map application for class VII material at SMP Negeri 2 Ambarawa. Furthermore, after carrying out development, validity and feasibility trials were carried out by media experts, material experts and learning practitioners and tested on students. This research uses the Research and Development (R&D) method in its development using the ADDIE model which includes analysis, design, development, implementation and evaluation stages. The learning products are mathematics teaching materials (LKPD), math city map applications, and lesson plans which are prepared based on learning on plane material. Mathematics teaching materials (LKPD), the Math City Map application and lesson plans are arranged based on indicators and the first expert gets scores respectively, namely 110, 180 and 96. The second expert gets scores respectively 100, 162 and 87. and the third expert 103, 163, and 88. The three scores obtained were in the valid category so that mathematics teaching materials assisted by the Math City Map application in class VII middle school flat figures material were suitable for use.